La participación de los padres de familia en el rendimiento académico de los niños y las niñas wayuu estudiantes de una institución etnoeducativa (2024)
Family participation in the educational environment is one of the main axes in the educational context of the child to be able to advance in their learning in order to achieve both their personal expectations as well as the interest of the parents for the good academic progress of the child, in Colombia many expectations have been generated about the influence of family participation in the improvement of the academic performance of students due to the fact that it encompasses factors that intervene in some way in that participation. The objective of this research study is to explore the different practices that parents make in the academic performance of children in an ethno-educational institution in La Guajira